The Influence of Motivation and Physical Work Environment on the Performance of PT Employees BPR Sari Jaya Sedana with Organizational Commitment as a Mediation Variable - RENY, Reny; SARA, I Made; DHARMANEGARA, Ida Bagus Agung (PT Keberlanjutan Strategis Indonesia, 2024)
In facing diverse competitors, companies must understand that the quality of performance does not only depend on technology, but also on the ability and motivation of its human resources. In order for human resource management, which according to experts is the art of managing employee relationships and roles effectively and efficiently, to be applied to an organization or company, management must also understand the motivation of employees, the ideal conditions of the physical work environment that employees expect and organizational commitment. created within an organization or company. This research aims to analyze the influence of Motivation, Physical Work Environment on Employee Performance through Organizational Commitment at PT. BPR Sari Jaya Sedana. The population used is all employees of PT. BPR Sari Jaya Sedana. The number of samples used was 30 employees with sampling techniques using saturated techniques. The data analysis used in this research is inferential analysis using SEM-PLS. The results of this research show that motivation has a positive and significant effect on employee performance. Motivation has a positive and significant effect on Organizational Commitment. The physical work environment has a positive and insignificant effect on employee performance. Physical Work Environment has a positive and significant effect on Organizational Commitment. Organizational Commitment has a positive and significant effect on Employee Performance. Organizational Commitment partially mediates (partial mediation) the influence of motivation on employee performance. Organizational Commitment is a perfect mediator between the influence of the Physical Work Environment on PT Employee Performance BPR Sari Jaya Sedana.